Two new species of Chaetocnema Stephens from South Africa (Coleoptera: Chrysomelidae, Galerucinae, Alticini) - Biondi, Maurizio; D'Alessandro, Paola (Fragmenta entomologica, 2018)
In this paper Chaetocnema adamastori sp. nov. and C. saldanhai sp. nov., both from Western Cape Province (Republic of South Africa), are described. The two new species are closely related with C. audisiana Biondi and C. capensis Bryant, respectively. Micrographs of diagnostic characters, including male and female genitalia, are supplied. Ecological data for each species, including habitat preference, host plant and phenology, are also reported.